Intensifying the sonochemical degradation of hydrophilic organic contaminants by organic and inorganic additives (2024)
ABSTRACT: The sonochemical system is highly effective at degrading hydrophobic substances but has limitations when it comes to eliminating hydrophilic compounds. This study examines the impact of organic and inorganic additiveson improving the sonochemical degradation of hydrophilic pollutants in water. The effects of adding an organic substance (CCl4) and two inorganic ions (Fe2+ and HCO3− ) were tested. The treatment was focused on a representative hydrophilic antibiotic, cefadroxil (CDX). Initially, the sonodegradation of CDX without additives was assessed and compared with two reference pollutants more hydrophobic than CDX: dicloxacillin (DCX) and methyl orange (MO). The results highlighted the limitations of ultrasound alone in degrading CDX. Subsequently, the impact of the additives on enhancing the removal of this recalcitrant pollutant was evaluated at two fre- quencies (375 and 990 kHz). A significant improvement in the CDX degradation was observed with the presence of CCl4 and Fe2+ at both frequencies. Increasing CCl4 concentration led to greater CDX elimination, whereas a high Fe2+ concentration had detrimental effects. To identify the reactive sites on CDX towards the species generated with the additives, theoretical calculations (i.e. Fukui indices and HOMO-LUMO gaps) were per- formed. These analyses indicated that the β-lactam and dihydrothiazine rings on CDX are highly reactive towards oxidizing species. This research enhances our understanding of the relationship between the structural charac- teristics of contaminants and the sonochemical frequency in the action of additives having diverse nature.